EFEKTIFITAS BEAUTY INFLUENCER TIKTOK DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN KOSMETIK MAYBELLINE NEW YORK - Dona Meliara Kurniawan; Deddy Aprilani; Hani Damayanti Aprilia (Jurnal Kompetitif Bisnis, 2023)
The modern society has close ties with social media, ranging from entertainment, the latest information to beauty trends. Beauty brands compete in attracting the attention of consumers through social media, and Tiktok as the most popular platfornm lately. The Maybelline Brand uses Beauty Influencers as the main key to successful promotion. The purpose of this study was to determine the influence of Laura Siburian as a Beauty The purpose of this study was to find out whether Laura Siburian as a Beauty Influencer Tiktok influences the purchasing decisions of her viewers or not. This research uses a type of quantitative researcher. The population of this study are active TikTok users who have watched Laura Siburian's promotional videos. The sampling technique used purposive sampling with a sample of 100 respondents. Data collection uses a questionnaire, with literature study through books, journals, and private or government publications. The analysis techniques used include validity test, reliability test, simple linear regression, t test, and R2 test with SPSS 24.0 tools. The results of this study are that the Beauty Influencer variable has a significant influence on purchasing decisions by 32.7%, the rest is explained by other factors. This proves that Laura can attract consumers' interest through her Tiktok promotional videos to make purchases of Maybelline mascara products effective and efficiently. In the future, the company can continue to improve collaboration with Beauty Influencer Laura Siburian and TikTok as its platform.